In situ investigation on the photoluminescence of 3D hierarchical branched CdS nanostructures coupling with Au nanoparticles. (30th August 2019) - Xu, Jinxia; Wang, Zhenhuan; Wu, Liming; Mei, Fei; Zhou, Yuanming; Jiang, Yan; Chen, Ying
Abstract: The hierarchical branched nanostructures have been widely studied for optoelectronics application due to their unique optical and electrical properties. Three-dimensional (3D) hierarchical branched Au-cadmium sulfide (CdS) nano-composite structures were successfully synthesized on Si substrate utilizing facile chemical vapor deposition (CVD) method combined with thermal evaporation method. Here, a simple in situ method combined with photolithography technology was carried out to investigate the photoluminescence (PL) 3D hierarchical branched CdS decorated with Au NPs. Compared with pure 3D hierarchical branched CdS, the PL emission of 3D hierarchical branched CdS decorated with Au NPs can be quenched and enhanced. The enhancement of the PL emission is attributed to the localized surface plasmons response (LSPR) of Au NPs, and the electrons transfer from Au NPs to CdS. While, the quenching is due to the light scattering of Au NPs, and the electrons transfer from CdS to Au NPs. The results can be used for in situ study of material properties, which is very important for the nano devices based on a single nanowire. And the results can also help to make clear the coupling mechanism of metal NPs and semiconductor. So, the PL emission quenching or enhancement of the metal NPs coupled with a semiconductor can be effectively controlled.